Testing for exogeneity in cointegrated panels - Trapani, Lorenzo (Wiley, 2015)
This paper proposes a test for the null that, in a cointegrated panel, the long-run correlation between the regressors and the error term is different from zero. As is well known, in such case the OLS estimator is T-consistent, whereas it is math formula-consistent when there is no endogeneity. Other estimators can be employed, such as the FM-OLS, that are math formula-consistent irrespective of whether exogeneity is present or not. Using the difference between the former and the latter estimator, we construct a test statistic which diverges at a rate math formula under the null of endogeneity, whilst it is bounded under the alternative of exogeneity, and employ a randomization approach to carry out the test. Monte Carlo evidence shows that the test has the correct size and good power.